Menakar loyalitas konsumen berdasarkan persepsi nilai dan kepercayaan merek geprek bensu - Sari, Novita; Marta, Rustono Farady; Angreani, Natasia; Harry, Harry; Perkasa, Muhammad Iman Adi (Universitas Dr.Soetomo, 2021)
To build high brand equity, a strong foundation is needed that is costumer loyalty to a brand. Brand loyalty can be assessed from various aspect and in this research, researcher used the value received by costumers and the trust of costumers. The purpose of this research is to examine the effect of perceived value and brand trust of brand loyalty â€œGeprek Bensuâ€ in Jakarta partially or simultaneously. In this research, the independent variable are perceived value (X1) and brand trust (X2) of Geprek Bensu in Jakarta, while the dependent variable is brand loyalty (Y). Population of this research is unlimited so it uses a sample of 130 respondents taken randomly (non-probability sampling) with a purposive sampling technique. The results of analysis SPSS can be concluded that perceived value and brand trust have a positive impact to brand loyalty partially and simultaneously with the result of T test for X1 is 2,055 and X2 is 7,604 which is grater than T tabel of 1,656. While the F test shows F count is 125,635 which has a higher figure than F table which is 3,07.